Coulomb Stress Changes in the 2004 Aceh Earthquake on the Mount Sibualbuali and Mount Lubukraya - Sinaga, Goldberd Harmuda Duva; Halawa, Analiser; Prasetyo, Retno Agung; Silaban, Irving Josafat Alexander; Sinaga, Mardame Pangihutan (Department of Physics Education, Universitas Mataram, 2024)
The great Aceh earthquake on December 26, 2004, had a magnitude of 9.2 Mw for 10 minutes with coordinates 3,316°N 95,854°E. had a tremendous impact on changes in geological conditions and disasters in Aceh and Asia, especially Southeast Asia and South Asia. Changes in geological conditions have resulted in Aceh and its surroundings becoming more prone to earthquakes, including volcanoes in North Sumatra. This research aims to determine the value of changes in coulomb stress that occur on Mount Sibualbuali and Lubukraya. This research uses the coulomb stress method presented in Coulomb 3.4 software. This research produces positive coulomb stress changes in 2021 which are marked by the red lobe, namely 0.197 bar on Mount Sibualbuali and 0.187 bar on Lubukraya. The highest increase in chwerees in coulomb stress was in 2015, namely 0.319 bar in Sibualbuali and 0.262 bar in Lubukraya. This research also resulted in the highest coulomb stress changes at a depth of 90-100 km so that it does not affect the volcanic activity of the two mountains.